A comparative study of banana chips made from different banana varieties - Villavicencio , Conny G. (2001.)
Three different varieties of bananas namely, Manilan-on, mundo, and tondal were processed into sweetened and salted banana chips.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana chips